OPTIMAL PRICING POLICY FOR MANUFACTURER AND RETAILER USING ITEM PRESERVATION TECHNOLOGY FOR DETERIORATING ITEMS - Khedlekar, U. K.; Nigwal, A. R.; Tiwari, R. K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
This paper optimizes the selling price, the replenishment cycle and lot size of deteriorating seasonal items. The seasonal items become useless or completely deteriorated after sale season. The production of manufacturer and stock of retailer are affected by deterioration and assuming it is reduced by preservation technology investment. Manufacturer and retailer both are invested on a preservation technology under revenue sharing. We studied the effect of preservation technology on profit of manufacture as well as for retailer. Retailer can change the strategy by reducing the selling price to generate the excess demand for limited time duration. This paper aims to develop a continuous supply chain inventory model by optimizing the selling price of seasonal items. We optimized the profit by reducing price for stock dependent price sensitive demand and have shown that the profit function is concave function of selling price. The model is simulated and illustrated with numerical examples.